DEVELOPMENT OF CANVA-BASED COMIC MEDIA TO IMPROVE THEMATIC LEARNING OUTCOMES THEME 1 GROWTH OF LIVING CREATURES CLASS III SDN NO 105348 PASAR V KEBUN KELAPA BERINGIN DISTRICT - Wardah Sholihah; Samsul Bahri (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to: (1) describe the development of Canva-based comic media in improving thematic learning outcomes for theme 1 Growth and development of living creatures in class III elementary school, (2) to describe the feasibility of Canva-based comic media in improving thematic learning outcomes for theme 1 Growth and development living creatures in class III elementary school. This research is a type of Research and Development (R&D) development research using the ADDIE development model. In this research, the researcher implemented the ADDIE development model only up to the development stage. The subjects in this research were material expert validators and media experts. The instrument used to collect data was a questionnaire. The data analysis technique used in this research is the Likert scale. Based on the validation results from material experts, namely 84.4% with very valid criteria, the results of validation by the media were 92% with very valid criteria and the validation results for teacher responses were 97% with very valid criteria.